2004
DOI: 10.5713/ajas.2004.777
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Forest Tree Leaves of Semi-hilly Arid Region as Livestock Feed

Abstract: Samples of 13 species of forest tree leaves fed to livestock in the semi-hilly arid zone of Punjab State in India were collected at 30 d interval for 12 months, in order to assess their nutritional worth for livestock. The ground samples were pooled for 4 different seasons viz. dry hot, hot humid, fall and winter. The chemical composition irrespective of the season revealed that CP content varied between 8.9 (Carrisa) to 22.0% (Leucaena). Globulin was the major protein fraction in most of the leaves. The lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 12 publications
3
37
1
1
Order By: Relevance
“…The crude protein content of crop residues and kitchen wastes in this study meets the requirement need of small ruminants as it is not less than 6% which will provide ammonia required by rumen microorganisms to support optimum microbial activity. They also contain reasonable amount of crude fibre which can be a good source since digestibility is dependent on the cell wall constituents (fibre), especially NDF (neutral detergent fibre) and lignin (Barkshi and Wadhwa, 2004). When crude fibre content is high, the energy and protein contents are lower because crude fibre is considered indigestible.…”
Section: Discussionmentioning
confidence: 99%
“…The crude protein content of crop residues and kitchen wastes in this study meets the requirement need of small ruminants as it is not less than 6% which will provide ammonia required by rumen microorganisms to support optimum microbial activity. They also contain reasonable amount of crude fibre which can be a good source since digestibility is dependent on the cell wall constituents (fibre), especially NDF (neutral detergent fibre) and lignin (Barkshi and Wadhwa, 2004). When crude fibre content is high, the energy and protein contents are lower because crude fibre is considered indigestible.…”
Section: Discussionmentioning
confidence: 99%
“…The digestion characteristics of the tree leaves of G. optiva revealed to be superior energy sources for ruminants (Singh et al 1989). A comprehensive study revealed that out of 13 species of forest tree leaves of Morusalba, Ehretialeavis, Grewia and Leucaenawere highly nutritious and showed great potential as alternate feed resources (Bakshi and Wadhwa, 2004). Similarly, in-vivo studies revealed that the leaves of high CP content fodder, Meliaazedarach, Morusalba and Leucaenaleucocephala supplemented with mineral mixture and common salt could be fed as complete feed to goat bucks (Bakshi and Wadhwa 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the fibre fraction in the diets shows that neutral detergent fibre (NDF), acid detergent fibre (ADF) and acid detergent lignin (ADL) were quiet high. It has been reported by Bakshi and Wadhwa (2004) that high levels of NDF and ADL have negative effect on DM intake and digestibility but increase ruminal rate of passage in ruminants. The apparent nutrient digestibility of West African Dwarf Sheep fed experimental diets is shown in Table 2.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%